ANALYSIS OF THE EFFECT OF OVERCONFIDENCE, HERDING EFFECT, SELF- MONITORING IN MANADO CITY - Claudia Vanesia Bagau; Kevin R. F. Wongkar; Nova D. Sihur; Olvianti Marsadu; Joubert B. Maramis (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2022)
This study aims to determine and analyze the effect of the level of confidence, the effect of hearing, and self-monitoring on investment decision making in the city of Manado. The independent variables in this study are self-confidence, auditory influence, and self-monitoring. As well as the dependent variable in this study, namely investment decisions. The population in this study are the people in the city of Manado, and the number of samples we took in this study were 31 people. This research was obtained from distributing research questionnaires to the people in the city of Manado. The type of research used in this research is quantitative research. The analytical method used in this study is the Statistical Program for Social (SPSS) by testing data and measurement variable values, AVE values, scree plot tests, AVE analysis, factor loading analysis, hypothesis testing and reliability analysis. The results of this study indicate that the three variables have a significant influence on investment decisions where the hypothesis testing proves that all hypotheses are not rejected. So that investors pay more attention to their investment decisions.